MHC class I-restricted cytotoxic lymphocyte responses induced by enterotoxin-based mucosal adjuvants. - Simmons, C; Mastroeni, P; Fowler, R; Ghaem-maghami, M; Lycke, N; Pizza, M; Rappuoli, R; Dougan, G (1999)
The ability of enterotoxin-based mucosal adjuvants to induce CD8+ MHC class I-restricted CTL responses to a codelivered bystander Ag was examined. Escherichia coli heat-labile toxin (LT), or derivatives of LT carrying mutations in the A subunit (LTR72, LTK63), were tested in parallel with cholera toxin (CT) or a fusion protein consisting of the A1 subunit of CT fused to the Ig binding domain of Staphylococcus aureus protein A (called CTA1-DD). Intranasal (i.n.) immunization of C57BL/6 mice with CT, CTA1-DD, LT, LTR72, LTK63, but not rLT-B, elicited MHC class I-restricted CD8+ T cell responses to coadministered OVA or the OVA CTL peptide SIINFEKL (OVA257-264). CT, LT, and LTR72 also induced CTL responses to OVA after s.c. or oral coimmunization whereas LTK63 only activated responses after s.c. coimmunization. rLT-B was unable to adjuvant CTL responses to OVA or OVA257-264 administered by any route. Mice treated with an anti-CD4 mAb to deplete CD4+ T cells mounted significant OVA-specific CTL responses after i.n. coadministration of LT with OVA or OVA257-264. Both 51Cr release assays and IFN-gamma enzyme-linked immunospot assays indicated that IFN-gamma-/- and IL-12 p40-/- gene knockout mice developed CTL responses equivalent to those detected in normal C57BL/6 mice. The results highlight the versatility of toxin-based adjuvants and suggest that LT potentiates CTL responses independently of IL-12 and IFN-gamma and probably by a mechanism unrelated to cross-priming.